Given:
The function is:
![f(x)=4x^5-8x^4+8x^2-4x](https://img.qammunity.org/2022/formulas/mathematics/high-school/3zz7lp64050n9gg05tttuw2sm6vdsjzt0a.png)
To find:
The roots of the given equation.
Solution:
We have,
![f(x)=4x^5-8x^4+8x^2-4x](https://img.qammunity.org/2022/formulas/mathematics/high-school/3zz7lp64050n9gg05tttuw2sm6vdsjzt0a.png)
For roots,
.
![4x^5-8x^4+8x^2-4x=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/j45rlu4ppeqy91b0px44get68ppkwyhbpb.png)
![4x(x^4-2x^3+2x-1)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/q0wi5fdk6gfr0pmtj9mqx650e5s8m5cv0u.png)
![4x((x^4-1)+(-2x^3+2x))=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/8sc2vg1s86doy13cvkokyiuzisuo6z99id.png)
![4x((x^2+1)(x^2-1)-2x(x^2-1))=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/bpwx7szcuh6siw6m1av3q7tz1uld11e3qr.png)
On further simplification, we get
![4x(x^2+1-2x)(x^2-1)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/157n5uvvfeqy9k02rb5wjlhhj1ca6g3uo9.png)
![4x(x-1)^2(x+1)(x-1)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/sfuuim47j4ct60ylp59zwsxjijznn20g0g.png)
![4x(x+1)(x-1)^3=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/gameidt6gph57xh4zqaa0mybef64b6sc9y.png)
Using zero product property, we get
![4x=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/v3po3s1xbhebihr9hmpho20tkdnkp8eeuk.png)
![x=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/va48jhxtyiee0xj3u2i8vp1i2h6dgdu35x.png)
Similarly,
![x+1=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/l7zzq4fkdaaah29f0s5qf23izj2ahah2vm.png)
![x=-1](https://img.qammunity.org/2022/formulas/mathematics/high-school/h6bj9u5fty63ngazrcsh28oi16zzymxgct.png)
And,
![(x-1)^3=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/8vxkznrjmihlj3721hu3hz3uqi7amdl6i4.png)
![x=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/x1mtktx3ckqtr9c9bhuvh92xozouexxxze.png)
Therefore, the zeroes of the given function are
and the factor form of the given function is
.